Partisipasi Masyarakat Dalam Mitigasi Bencana Banjir Di Nagari Durian Tinggi Kecamatan Lubuk Sikaping Kabupaten Pasaman - Alwiyah Nur Auliya; Erna Juita; Rozana Eka Putri (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2024)
Disasters are events that threaten and disrupt people's lives and livelihoods caused by various factors resulting in casualties, environmental damage, property losses, etc. This study aims to determine 1) the level of participation, 2) information and communication in flood disaster mitigation efforts, 3) decisions and planning in flood disaster mitigation efforts. This type of research is Quantitative Descriptive using proportional random sampling data collection techniques using observation, interviews, questionnaires, and documentation. Then the data analysis technique uses percentage and Likert scale. The results of the study are: 1) The level of community participation in flood disaster mitigation efforts in Nagari Durian Tinggi, Lubuk Sikaping District, Pasaman Regency is good with a percentage of 69.36%. 2) community participation in information and communication of flood disaster mitigation efforts in Nagari Durian Tinggi, Lubuk Sikaping District, Pasaman Regency is good with a percentage of 70.27%. 3) Community participation in the decision-making and planning process in flood disaster mitigation efforts in Nagari Durian Tinggi, Lubuk Sikaping District, Pasaman Regency is good with a percentage of 70.02%.